Implementation Adaptation Curriculum in Increase Quality Learning - Munif; Muh Habibulloh; Himad Ali (CV. Gerasi Insan Nusantara, 2024)
Research This discuss implementation adaptation curriculum in increase quality learning at school middle in the Regency Jombang. With use approach qualitative and methods studies case, research This exploring adaptation strategies curriculum implemented by the school, challenges faced, and​ the impact on the learning process. Data collected through interview in-depth, observation, and analysis document related. Research result show that adaptation curriculum done through various strategies, such as adjustment material learning in accordance with need students, use method innovative like blended learning and project-based learning, as well collaboration with party external. Adaptation This proven increase involvement students and enrich experience Study them. However, the challenges main issues faced school covering limitations source power, change policy fast curriculum, as well as teacher and student readiness in apply approach new. Although face various constraints, adaptation curriculum impact positive to improvement quality learning. Students become more active, have understanding more concept​ good, and develop skills think critical and solving problem. Besides that, system evaluation more learning​ varied and based the project also became indicator success implementation adaptation curriculum. Study This recommend the need more policies​ flexible, improvement training for teachers, as well as support adequate infrastructure​ For ensure effectiveness and sustainability adaptation curriculum. With Thus, the environment learn more​ responsive and quality can created For support development student optimally.